Nickel metal hydride ready to serve. - Stempel, R.C (IEEE spectrum)
With their impressive energy performance and their outstanding power capability, Ni-MH batteries are equally suitable for use in pure and hybrid electric vehicles. This is due to the basic nickel-metal hydride technology. For one thing, hydrogen can be stored in metal-hydride alloys at very high volumetric densities, comparable to the density in liquid hydrogen, leading to the superior energy density of metal-hydride batteries. The operating principles of the Ni-MH battery are described as is their construction and manufacture. The on-road performance of Ni-MH batteries and hybrid electric vehicle batteries are discussed